Implementasi Pendidikan Karakter Berbasis Kearifan Lokal Hasthalaku di SMA N 1 Surakarta - Feri Dwi Jayanti; Taat Wulandari (Jurnal Pendidikan dan Pengajaran, 2024)
The increase in corruption cases, the increasing number of cases involved in drugs and various forms of juvenile delinquency are the impact of the erosion of the character that is owned and held firmly by the Indonesian people. One solution that schools can implement is to implement character education based on local Hasthalaku wisdom. This research aims to analyze the implementation of character education based on local wisdom in high schools. The research subjects consisted of the deputy principal, Hasthalaku teacher, several subject teachers, and several students at the school. The research was conducted using naturalistic qualitative methods. Data collection used passive participant observation techniques, semi-structured interviews, and documentation. The analysis technique uses technical triangulation and triangulation of research data sources. Data analysis uses an interactive model developed by Miles and Huberman, including three procedures: data condensation, data presentation, and conclusion drawing. The research results show that character education based on local Hasthalaku wisdom has been implemented consistently and sustainably through several school programs/activities. The school's efforts to implement character education based on local Hasthalaku wisdom can shape students' character by the character of Javanese society. The implications of this research can have a positive impact on students' lives now and in the future.